BRIDGING ENGLISH INSTRUCTION AND CRITICAL THINKING: A NEEDS ANALYSIS AT TWO ISLAMIC HIGHER EDUCATION INSTITUTIONS IN INDONESIA - Sandi Pradana; Ifan Awanda (University of Kuningan, 2025)
This study specifically examines the English teaching material needs of lecturers at STIT Tanggamus and STIT Pringsewu to enhance students’ critical thinking skills. Recognizing that critical thinking is an essential competence in higher education, particularly in English language learning, this research adopts a mixed-methods design to explore the types of materials currently in use, lecturers’ perceptions of students’ critical thinking abilities, and the gaps between existing resources and instructional needs. The study employed a mixed-methods approach, utilizing questionnaires, semi-structured interviews, and document analysis for data collection. The findings highlight a prevalent reliance on authentic materials, underscoring the need for explicit critical thinking frameworks and contextual relevance within the Islamic educational environment. Lecturers expressed concerns regarding students’ limited critical thinking capacity, citing language barriers, insufficient scaffolding, and lack of pedagogical support. It is crucial to redesign English teaching materials systematically to integrate higher-order thinking tasks, align with students' cultural and religious backgrounds, and provide clear instructional guidance. The findings highlight the essential requirements for both material development and professional training to enhance the cultivation of critical thinking in English language education within Indonesian Islamic higher education institutions.